Nondiscrimination Policy and Privacy Protection in Case of Genetic Passport for Soldiers - Raissova, Gulshat; Mukhamejanova, Dana (South Asian Journal of Social Sciences and Humanities, 2021)
It is difficult now to imagine the field of life, where genetic technologies have not been used. In Russia, there are already genetic passports of athletes, which made it possible to identify so-called "sports genes" that can predict individuals' inclination to a particular sport. In the United States of America, the Department of Defense (DOD) collects and uses the genetic information of all U.S. service members, including active duty and reserve military personnel. This article aims to explore the connection between genetic discrimination and protection of privacy. Whether the accessibility of such genetic data at the disposal of third parties will not lead to violations of their privacy that could further result in genetic discrimination? Basic human rights instruments in domestic and international law that regulates the right to non-discrimination and right to privacy will be reviewed beneath.
Keywords: Genetic discrimination; genetic passport; human rights; privacy; data protection